2016
DOI: 10.1590/s0034-759020160608
|View full text |Cite
|
Sign up to set email alerts
|

Creative Marketing Strategy and Effective Execution on Performance in Pakistan

Abstract: The purpose of the current research is to determine the influence of creative marketing strategies and effective execution on business unit performance. Moreover, strategic orientation and environmental uncertainty are used as moderating variables. Data are collected from 368 key informants working in Fast-Moving Consumer Goods (FMCG), banking, pharmaceutical, chemical, insurance, and engineering industries using a multi-stage random sampling technique. Factor analysis and multiple hierarchal regressions are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Other findings by (Ishaq and Hussain, 2016) show that the choice of creative marketing strategies has had a positive impact on company performance. Previously, (Andrews and Smith, 1996) concluded that creative marketing strategies had a significant impact on the firm's business performance.…”
Section: Relation Of Novelty and Meaningfulness Of Digital Marketing On Hotel Performancementioning
confidence: 94%
See 4 more Smart Citations
“…Other findings by (Ishaq and Hussain, 2016) show that the choice of creative marketing strategies has had a positive impact on company performance. Previously, (Andrews and Smith, 1996) concluded that creative marketing strategies had a significant impact on the firm's business performance.…”
Section: Relation Of Novelty and Meaningfulness Of Digital Marketing On Hotel Performancementioning
confidence: 94%
“…Creative marketing strategies are activities that are developed to promote products/services that selectively target markets and support the achievement of the company's business goals (Ishaq and Hussain, 2016). Therefore (Ishaq and Hussain, 2016) explained that marketing creativity is a step towards the conception of typical practices in the company's marketing function. Creative marketing is needed to provide a complete understanding of how companies work effectively to conduct sales practices (Terkan, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations